A comprehensive study on development of a biocathode for cleaner production of hydrogen in a microbial electrolysis cell - Jafary, T. (Elsevier Ltd, 2017)
A biocathode microbial electrolysis cell (MEC) can be considered as an environmentally friendly and self-generative alternative to an abiocathode MEC for the cleaner production of hydrogen in a novel microbial electrolysis system. For the first time, this research focused on the development of the MEC biocathode out of sulphate-reducing bacteria (SRB) for the purpose of hydrogen production based on the previously proposed hypothesis. SRB were initially enriched from a mixed culture source during the ex-situ SRB enrichment stage. Two different MEC bioathodes- namely, the MEC origin (MEC-O) biocathode and the microbial fuel cell-MEC (MFC-MEC) biocathode- were then developed through two different enrichment procedures during the in-situ SRB enrichment stage. Hydrogen gas was the main product of the MEC-O biocathode with a low detection of methane, while methane was detected as the sole product of the MFC-MEC biocathode system. Therefore, the MEC-O biocathode system was selected during the enhancement stage to increase the biocathode MEC performance. It was shown in the study, that in the enhancement stage of the MEC-O biocathode, the concentration of sodium sulphate in the cathodic medium, the hydrogen supply during the enrichment stage and pH of the cathodic medium could significantly affect the MEC performance in terms of the hydrogen production rate, the onset potential for the hydrogen evolution reaction (HER) and the cathodic charge transfer resistance. The hydrogen production was improved significantly by about 6 times from 0.31 to 1.85 m3 H2/(m3 d) during the enhancement stage, while the methane production was totally hindered. The linear sweep voltammetry analysis displayed a 430-mV (equal to about 1 kWh/m3 of energy input) reduction of the HER onset potential in the biocathode system compared to that of a non-inoculated graphite felt cathode. Moreover, the electrochemical impedance spectroscopy showed that the cathodic charge transfer resistance of the MEC biocathode reduced by 300 times compared to that of a non-inoculated graphite felt cathode. © 2017 Elsevier Ltd